Teachers’ perceptions toward TED-ED in Listening Class insight the Era of Disruptive Technology - Candradewi Wahyu Anggraeni; Lilia Indriani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
Abstract In the era of disruptive technology in the educational aspect, the teachers need to pay attention to the use of technology in teaching and learning process. Technology can be virtues or hurdles for the students and teachers. Therefore, the teachers must be wise in deciding the teaching strategies so that the use of technology in the classroom will be more effective and efficient. One of the examples of technology is the existence of a website or online media to support teaching and learning process. Regarding this phenomenon, this study is carried out to explore the teachers’ perceptions toward TED-ED in listening class insight the era of disruptive technology. The qualitative research method in the form of a case study is used to expose the teachers’ perceptions. The instrument of data collection is an open-ended interview. The findings show that there are two perspectives toward the use of TED-ED in Listening Class. The two perceptions reveal the benefits and drawbacks that cover the aspects of abundant resources, illustration, world Englishes, assignments, speed, and teacher’s role. This study has theoretical, pedagogical, and practical significances in the field of teaching Listening.